ДІАЛОГ НА УРОЦІ ІНОЗЕМНОЇ МОВИ ЯК ШЛЯХ ДО РЕАЛІЗАЦІЇ ОСОБИСТІСНО-РОЗВИВАЛЬНОГО НАВЧАННЯ (Педагогіка вищої та середньої школи, 2004)
In this article forming of dialogue culture among students is considered, and solving of the problem is in group activity of pupils at the foreign language lesson.